The Durable, Dynamic Nature of Genre and Science: A Purpose‐Driven Typology of Science Trade Books. Issue 3 (24th September 2019) - May, Laura; Crisp, Thomas; Bingham, Gary E.; Schwartz, Renée S.; Pickens, Mario T.; Woodbridge, Kate
Abstract: The authors conducted a qualitative content analysis of the 400 National Science Teachers Association Outstanding Science Trade Books for Students K–12 from 2010–2017 selected for their instructional usefulness in science classrooms. The authors examined these expert‐recommended science trade books to better understand their design and to identify the various aspects of science education to which various genres may contribute. In light of previous research demonstrating the importance of texts used in science classrooms, the authors attended to the books' scientific discourses and features. The authors present a typology helpful for understanding the books as related to science education broadly. The authors found general alignment between books that use expository language and those genres most likely to present knowledge accepted as reliable by the relevant scientific community. Genres apt to support the development of understandings about the nature of science and scientific inquiry, however, were more often composed of narrative. Given the richness of the text set and the multiple discourses therein, the authors were unable to bring their typology into alignment with arguments that certain kinds of trade books are unsuitable for science classrooms (e.g., biography, realistic fiction). A challenge with much of the existing research on science trade books and their use is that it has used oversimplified binary categories of narrative/expository to encourage limiting exposure to a single discourse or genre. Ultimately, through the typology presented, the authors seek to support the ability of science educators and researchers in identifying how different types of science trade books align with comprehensive science education.